2018
DOI: 10.1103/physrevd.98.063502
|View full text |Cite
|
Sign up to set email alerts
|

Simulated reconstruction of the remote dipole field using the kinetic Sunyaev Zel’dovich effect

Abstract: The kinetic Sunyaev Zel'dovich (kSZ) effect, cosmic microwave background (CMB) anisotropies induced by scattering from free electrons in bulk motion, is a primary target of future CMB experiments. In addition to shedding light on the distribution of baryons and the details of the epoch of reionization, measurements of the kSZ effect have the potential to address fundamental questions about the structure and evolution of our Universe on the largest scales and at the earliest times. This potential is unlocked by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In this section we assess the performance of velocity reconstruction with future datasets using a suite of simulations and a reconstruction pipeline based on the quadratic estimators described in previous sections. Previous work has demonstrated the effectiveness of the quadratic estimator for reconstruction of the radial velocity field using N-body simulations both on the light cone [45] and in the box geometry [43]. There has been no previous work demonstrating the feasibility of transverse velocity potential reconstruction with the moving lens effect, a gap which we fill with the present work.…”
Section: Velocity Reconstruction Pipelinementioning
confidence: 87%
See 2 more Smart Citations
“…In this section we assess the performance of velocity reconstruction with future datasets using a suite of simulations and a reconstruction pipeline based on the quadratic estimators described in previous sections. Previous work has demonstrated the effectiveness of the quadratic estimator for reconstruction of the radial velocity field using N-body simulations both on the light cone [45] and in the box geometry [43]. There has been no previous work demonstrating the feasibility of transverse velocity potential reconstruction with the moving lens effect, a gap which we fill with the present work.…”
Section: Velocity Reconstruction Pipelinementioning
confidence: 87%
“…Aside from this bias, both Refs. [43] and [45] demonstrated that velocity reconstruction essentially works as advertised even for non-linear N-body simulations. An important future analysis will be to directly compare the importance of the various systematic effects discussed in this paper between Gaussian and non-linear N-body simulated datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scheme is based on Eq. ( 31), but does not require radial binning or extracting the gravitational potential, and has been employed in a number of contexts in the literature [78][79][80][81][82],…”
Section: E Theory Of Lensing and Isw Effectsmentioning
confidence: 99%
“…By combining future optical surveys (such as DESI DESI Collaboration et al 2016, Euclid Amendola et al 2018and LSST LSST Science Collaboration et al 2009) and Cosmic Microwave Background (CMB) experiments (such as the future Simons Observatory Ade et al 2019 andCMB-S4 Abazajian et al 2016) the radial peculiar velocities can be measured with high precision from the kSZ effect imprinted on the CMB for millions of galaxies and can be used to constrain cosmological parameters (e.g. Smith et al 2018;Münchmeyer et al 2018;Deutsch et al 2018;Cayuso et al 2018;McCarthy & Johnson 2019;Pan & Johnson 2019).…”
Section: Introductionmentioning
confidence: 99%